2011
DOI: 10.1189/jlb.0111036
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin-induced uveitis is primarily dependent on radiation-resistant cells and on MyD88 but not TRIF

Abstract: TLR4 activation by LPS (endotoxin) is mediated by the MyD88 and TRIF intracellular signaling pathways. We determined the relative activation of these pathways in murine ocular tissue after LPS exposure. Additionally, we explored whether BM-derived or non-BM-derived cells were the major contributors to EIU. Mice deficient in TRIF or MyD88 and their congenic (WT) controls received 250 ng ultrapure LPS ivt at 0 h. Ocular inflammation was assessed by histological analysis at 4, 6, and 24 h, and additionally, in My… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…At the indicated times, mice were killed, and the eyes, ankles and knees were dissected, fixed in 10% neutral-buffered formalin, and prepared for paraffin embedding and sectioning as previously reported 25 26. Tissue sections (7 µm thick) were stained with H&E, and the severity of inflammatory changes was quantified by a masked observer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the indicated times, mice were killed, and the eyes, ankles and knees were dissected, fixed in 10% neutral-buffered formalin, and prepared for paraffin embedding and sectioning as previously reported 25 26. Tissue sections (7 µm thick) were stained with H&E, and the severity of inflammatory changes was quantified by a masked observer.…”
Section: Methodsmentioning
confidence: 99%
“…Dissected ankles, knees and eyes were homogenised in lysis buffer containing protease inhibitors 25 27. Protein concentrations were quantified by BCA assay (BioRad, Hercules, California, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In an endotoxin-induced uveitis (EIU) mouse model, the TLR4/MyD88-dependent pathway contributed to inflammation (43)(44)(45). However, in the EIU model, some of TRIFdependent cytokines were found to be proinflammatory (46), while other TRIF-dependent cytokines were anti-inflammatory (43,47).…”
Section: Fig 9 Proinflammatory Mediator Expression In Tlr4mentioning
confidence: 99%
“…In an endotoxin-induced uveitis (EIU) mouse model, the TLR4/MyD88-dependent pathway contributed to inflammation (43)(44)(45). However, in the EIU model, some of TRIFdependent cytokines were found to be proinflammatory (46), while other TRIF-dependent cytokines were anti-inflammatory (43,47). In Pseudomonas aeruginosa keratitis models, MyD88-and TRIF-mediated signaling following LPS recognition by TLR4 has been reported (48)(49)(50).…”
Section: Fig 9 Proinflammatory Mediator Expression In Tlr4mentioning
confidence: 99%
“…In addition, expression of TLR2 in human conjunctival epithelial cells was shown to play a significant role in the chronic ocular inflammatory response to Staphylococcus aureus [3]. Kezic et al [4] suggested that both epithelial cells and immune cells play a role in ocular inflammation. Specifically, radiation-resistant, non-bone marrow derived ocular cells, such as iris endothelial cells or nonpigmented ciliary body epithelial cells, play a greater role in the development of endotoxin-induced uveitis (EIU) than bone marrow-derived macrophages and dendritic cells residing in the eye [4].…”
Section: Introductionmentioning
confidence: 99%